2023
DOI: 10.1186/s12888-023-04697-w
|View full text |Cite|
|
Sign up to set email alerts
|

Marital status and gambling disorder: a longitudinal study based on national registry data

Abstract: Background Marital status is a robust correlate of disordered gambling, but few studies have examined the direction of this association. Methods The present study used a case–control design by including all adults receiving their first gambling disorder (GD) diagnosis between January 2008 to December 2018 (Norwegian Patient Registry, n = 5,121) and compared them against age and gender matched individuals with other somatic/psychiatric illnesses (No… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 52 publications
(79 reference statements)
0
2
0
Order By: Relevance
“…Our results are more consistent with recent studies, which have shown that the gender difference in gambling may be narrowing (41,42). Marital status and living with other people were associated with higher quality of life and can be seen as a protective factor for GD (43). The results suggest that although sociodemographic factors are associated with gambling and gambling severity, their effect on treatment outcomes may be inconsistent.…”
Section: Discussionsupporting
confidence: 90%
“…Our results are more consistent with recent studies, which have shown that the gender difference in gambling may be narrowing (41,42). Marital status and living with other people were associated with higher quality of life and can be seen as a protective factor for GD (43). The results suggest that although sociodemographic factors are associated with gambling and gambling severity, their effect on treatment outcomes may be inconsistent.…”
Section: Discussionsupporting
confidence: 90%
“…Other important factors not included in the model may have helped in further understanding characteristics that differentiate between trajectory group membership. For example, potential individual characteristics such as marital or immigration status, in addition to area-level characteristics including socioeconomic deprivation, rural-urban dwelling, and accessibility of gambling opportunities have been associated with GD ( Allami et al, 2021 ; Hahmann et al, 2021 ; Syvertsen et al, 2023 ) and may further help to differentiate group membership, particularly related to the highest versus lowest income groups. The prevalence of GD may also vary in terms of geographical locations.…”
Section: Discussionmentioning
confidence: 99%
“…Following the publication of the original article [ 1 ], multiple errors were identified in the sections and Tables 1 and 2 . The correct tables are given below and the changes in the abstract, results and discussion sections have been highlighted in bold typeface .…”
mentioning
confidence: 99%